2021
DOI: 10.1007/s10719-021-10023-x
|View full text |Cite
|
Sign up to set email alerts
|

Glycosphingolipid metabolism and its role in ageing and Parkinson’s disease

Abstract: It is well established that lysosomal glucocerebrosidase gene (GBA) variants are a risk factor for Parkinson’s disease (PD), with increasing evidence suggesting a loss of function mechanism. One question raised by this genetic association is whether variants of genes involved in other aspects of sphingolipid metabolism are also associated with PD. Recent studies in sporadic PD have identified variants in multiple genes linked to diseases of glycosphingolipid (GSL) metabolism to be associated with PD. GSL biosy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 127 publications
0
12
0
Order By: Relevance
“…Cholesterol in the brain can be cleared to the blood either directly by reverse transport using glial apolipoprotein E (APOE) or after metabolic conversion to 24Shydroxycholesterol predominantly by neuronal cytochrome P450 family 46 subfamily A group 1 (CYP46A1) enzyme activity [17]. In a similar manner to cholesterol, each brain cell type synthesises and uses patterns of intracellular sphingolipids, and these patterns can change with age [5,[18][19][20][21]. Microglia in particular alter the expression of enzymes that metabolise sphingolipids during different inflammatory states while not synthesising cholesterol.…”
Section: Circuit Levelmentioning
confidence: 99%
“…Cholesterol in the brain can be cleared to the blood either directly by reverse transport using glial apolipoprotein E (APOE) or after metabolic conversion to 24Shydroxycholesterol predominantly by neuronal cytochrome P450 family 46 subfamily A group 1 (CYP46A1) enzyme activity [17]. In a similar manner to cholesterol, each brain cell type synthesises and uses patterns of intracellular sphingolipids, and these patterns can change with age [5,[18][19][20][21]. Microglia in particular alter the expression of enzymes that metabolise sphingolipids during different inflammatory states while not synthesising cholesterol.…”
Section: Circuit Levelmentioning
confidence: 99%
“…The mechanism by which GBA1 mutation carriers increase the risk of PD is not fully understood. Reduced GCase activity has been described in brain tissues of PD patients with and without GBA1 mutations 3‐5 as well as in healthy aging subjects, 3,6,7 but a recent study showed no correlation between total GCase activity and PD risk 8 . Overall, the role of GSLs in sporadic PD, independently from GBA1 ‐related disorder, needs broader examination and further clarification.…”
mentioning
confidence: 99%
“…Our first unexpected finding was that most lysosomal enzyme activities do not correlate with their mRNA levels, nor with most of their substrate levels. Although enzyme activity can decrease with age 58 , we used sex and aged-matched samples; thus, the variation observed across strains is not due to any of these factors. Our results therefore suggest that GSL biosynthesis rate and uptake differ across the mouse strains, suggesting the existence of specific modifier genes for each trait.…”
Section: Discussionmentioning
confidence: 99%